EKSISTENSI PEREMPUAN PEMBUAT PERIUK DARI TANAH LIAT DI DESA LAPOLE KECAMATAN MALIGANO KABUPATEN MUNA - La Ahmad Syarif; Wa Ode Sifatu; Zainal Zainal (KABANTI : Jurnal Kerabat Antropologi, 2023)
This research aims to describe the existence of women who make pots from clay in Lapole Village, Maligano District, Muna Regency. In addition, this study also used the ethnographic method. Data collection was carried out using observation techniques and in-depth interviews. There are currently only 7 female prick makers left and they are also classified as people who are entering the elderly age, where the prick makers have an average age of 50 to 72 years, at this age they still make prick with knowledge. and modest tools. The millennial generation's lack of involvement and knowledge of traditional cooking utensils is deplorable because it can eliminate one of the cultural heritages given by their ancestors. The government's role is also very much needed in cultural preservation, namely as a protector, policy maker, and facilitator supporting national culture preservation. The hope is that the original culture of the Indonesian nation can be maintained so that the prick as a traditional cooking utensil will not become extinct from modern human civilization. The existence of prick makers in modern times is starting to be lacking. However, prick makers are still making this prick due to several orders from neighboring villages, so prick makers are still making them but are limited so it can be said that this prick cannot be marketed widely.